Radiographic cephalometry analysis of head posture and craniofacial morphology in oral breathing children - Vukićević, Vladanka; Pavlović, Jasna; Vujačić, Amila; Martinović, Brankica; Kostić, Mirjana; Staletović, Danijela (Vojnosanitetski pregled, 2017)
Background/Aim. Nasal breathing plays an important role in overall physical growth and mental development, as well as in the growth of the craniofacial complex. Oral breathing over a long period of time, can cause changes in position of the head relative to the cervical spine and jaw relationship. It can cause an open bite and the narrowness of the maxillary arch due to increased pressure of strained face. The aim of this study was to analyze the position of the head and craniofacial morphology in oral breathing children, and compare the values obtained compared with those of the same parameters in nasal brething children. Methods. We analyzed the profile cephalometric radiographs of 60 patients who had various orthodontic problems. In the first group there were 30 patients aged 8–14 years, in which oral breathing is confirmed by clinical examination. In the second group there were 30 patients of the same age who had orthodontic problems, but did not show clinical signs of oral breathing. The analyses covered the following: craniocervical angle (NS/OPT), the length of the anterior cranial base (NS), anterior facial height (N-Me), posterior facial height (S-Go), the angle of maxillary prognathism (SNA), angle of mandibular prognathism (SNB), difference between angles SNA and SNB (ANB angle), the angle of the basal planes of the jaws (SpP/MP), cranial base angle (NSB), and the angle of facial convexity (NA/Apg). Results. The average value of the craniocervical angle (NS/OPT) was significantly higher in OB children (p = 0.004). There were significantly different values of SNA (p < 0.001), ANB (p < 0.001), NA/APg (p < 0.001) and length of the anterior cranial base (NS) (p = 0.024) between groups. Conclusion. Oral breathing children have pronounced retroflexion of the head in relation to the cervical spine compared to nasal breathing children, and the most prominent characteristics of the craniofacial morphology of skeletal jaw relationship of class II and increased facial convexity.